Performance Improvement of TiO2/CuO Solar Cell by Growing Copper Particle Using Fix Current Electroplating Method. (2017) - Rokhmat, Mamat; Wibowo, Edy; Sutisna,; Khairurrijal,; Abdullah, Mikrajuddin
Abstract: Here, we report the efficiency enhancement of TiO2 /CuO/Cu/PVA.LiOH/Al solar cell by growing copper particles on the space between TiO2 and/or CuO particles. The TiO2 /CuO film was developed by spraying process of TiO2 /CuO suspension to the Fluorin doped Tin Oxide (FTO), while copper particles were grown by fix current electroplating as our proposed method. We found the highest efficiency and fill factor was 1.62% and 0.42, respectively. This result is higher than by using fix voltage electroplating (ordinary electroplating) as we reported in a previous paper. We suspect that the presence and the optimum amount of copper particles can improve efficiency and fill factor of the solar cells because it can facilitate the transporting process of electrons to the electrode. The effect of the magnitude of the current and time of electroplating is also investigated. The highest efficiency is obtained by using electroplating current of 10 mA for 20 seconds, which gives the amount of copper content of 7.6%. It indicates that the copper content of this magnitude is sufficient to improve the transport of electrons.